A retained dead fetus for eight years in a didelphys uterus - Pant, PR; Sharma, J; Giri, K; Pradhan, N; Thapa, TP (Journal of Institute of Medicine Nepal, 2007)
Case report: A case report of 32 years female with 3 childrens and a retained dead fetus for eight years in a didelphys uterus is discussed as a case report Key words: Didelphys uterus, dead fetus, coagulopathy The full text of this paper is available at Journal of Institute of Medicine website